SCREENING FOR EARLY DETECTION OF BREAST CANCER - E. A. Rasskazova (Issledovaniâ i Praktika v Medicine, 2015)
The article presents a brief overview of the main methods of breast cancer screening. Proven effectiveness of mammography as a screening method in reducing mortality from breast cancer, specified limits of the method. The main trend of increasing the effectiveness of screening is the transition to digital technologies. Properly organized screening with the active participation of the population reduces mortality from breast cancer by 30%.